Short-Term Effects of Radiotherapy Postquadrantectomy on Internal Mammary Artery and Vein. (4th March 2013) - Cherubino, Mario; Scamoni, Stefano; Taibi, Dominic; Maggiulli, Francesca; Pellegatta, Igor; Izzo, Matteo; Valdatta, Luigi
Abstract : When a tumor local recurrence occurs a possible approach can be a mastectomy with simultaneous breast reconstruction with autologous tissue. The area involved by tangential radiation portals includes also the internal mammary artery and veins, considered by the most part of plastic surgeons to be the best recipient vessels for a free flap in breast reconstruction. Internal mammary vessels receives low but not necessary insignificant doses during whole breast irradiation; arteries and veins are traditionally considered quietly resistant to the irradiation but limited data on the flux in mammary vessels after radiotherapy are available. The goal of our study (37 patients from September 2011 to February 2012) was to evaluate modifications in vascular parameters of the flux at ultrasonography in the internal mammary chain after adjuvant radiotherapy that could influence the choice of the autologous surgical technique (free or pedicled flap) and the choice of the recipient vessels in breast reconstruction. Based on the results of our study, we would recommend avoiding an irradiated recipient site when no irradiated recipient vessels are available; a preoperative ultrasound evaluation is recommended in patients underwent whole breast irradiation.